Construing The Great Fire of London through online media: A case of exploring discourse semantics and register - Bangga, Lungguh Ariang (Indonesian Journal of Applied Linguistics, 2020)
This paper considers the exploration of genre and register of historical texts recontextualised in online media and school textbooks through the lens of Systemic Functional Linguistics especially by exploring their discourse semantics and register features. Particularly, this paper shows how the relation between discourse semantics resources and register variables contribute to the overall organisation of the recontextualized history genres. This paper provides a detailed qualitative analysis of discourse semantics as instantiated in the deployment of APPRAISAL, IDEATION, IDENTIFICATION, and PERIODICITY to give a clearer picture of how history genres in the media are established. A set of corpora consisting of historical texts from online media and school textbooks was used as a main source of data in this study. The historical texts collected from online media were from various platforms including online newspapers, online magazines, encyclopaedia entries, and universities websites/blogs. For the illustrative purposes, two texts from the corpora were selected for a detailed analysis using the discourse semantics toolkits to find out similarities and differences in terms how an historical event – The Great Fire of London – was established.  The analysis found that there was a tendency that historical events could be reconstrued in the media through different ways. The first text informs readers about the fire and its significance in a chronological manner. The second text provides an explanation of the influence of the Great Fire to other historical events. This paper also suggests that history genres tend to be ‘evolving’ as reproduced in varied media discourses. Though still at the infancy stage, this paper offers a great insight into how genres are organised in relation to the choices in register variables and discourse semantics.